(3OQGSI JCUjdjI JMdjdjI aj GdEYJQGV Ydi Mce GdGadGS hGSJFfGag Ydi VhA GdGJLGgGJ GdMOjKI aj bGfhf GdJLGQI GdLOjO Qbe (B17(3dSfI (B1999s - (3WdYJ eMeO(B, (3OhjOGQs ((3GdGScfOQjI(B:s (3OGQ GdLGeYI GdLOjOI(B,s, 2003)
(3JCUjd Cge ETcGdjGJ GdHMK,GdGJLGgGJ GdMOjKI aj GdJfXje GdGLQGFj ddEadGS,GdWHjYI GdafjI dMce GdGadGS,GdWHjYI GdafjI dGYJQGV GdZjQ Ydi Mce GdGadGS,GdNUhe aj GdWYf aj Mce GdGadGS,KHhJ Mb GdWYfaj Mce GdGadGS dCWQGa NUheI GdGadGS,eaghe GdZjQ UGMH GdUaI aj GdGYJQGV Ydi Mce GdGadGS,Tcd GdWYf aj Mce GdGadGS,GdeMceI GdeNJUI HGYJQGV GdZjQ Ydi Mce GdGadGS,ehGYjO GdWYf aj Mce GdGadGS,WQjbI QaY GdGYJQGV GdZjQ aj Mce GdGadGS,eMd GdWYf hBKGQg, eMd GdWYfs
(3HHdjhZQGajG U(B.187s
Keywords: (3GdEadGS (B- (3bhGfjf hJTQjYGJs; (3GdGadGSs